A COMPARATIVE STUDY BETWEEN MIPH VERSUS OPEN HAEMORRHOIDECTOMY - JAIN, PIYUSH; JAIN, SUNIL KUMAR (International Journal of Current Pharmaceutical Research, 2025)
Objective: Hemorrhoidal disease is a prevalent anorectal disorder that significantly impacts patients' quality of life. Surgical intervention, including Minimally Invasive Procedure for Hemorrhoids (MIPH) and Open Hemorrhoidectomy, plays a crucial role in managing symptomatic hemorrhoids. However, the comparative effectiveness and safety of these surgical techniques remain debated. Methods: This retrospective cohort study compared the clinical outcomes, safety profile, and cost-effectiveness of MIPH versus Open Hemorrhoidectomy. A total of 130 patients diagnosed with symptomatic hemorrhoids underwent either MIPH or Open Hemorrhoidectomy at our institution. Data on demographic characteristics, presenting complaints, degree of hemorrhoids, operative outcomes, and postoperative complications were collected and analyzed. Statistical analysis was performed using appropriate tests to compare outcomes between the two groups. Results: The study included 65 patients in each group (MIPH and Open Hemorrhoidectomy). MIPH was associated with shorter mean duration of surgery, reduced postoperative bleeding and intraoperative blood loss, shorter hospital stay, lower incidence of residual prolapse, faster wound healing, and quicker return to work compared to Open Hemorrhoidectomy. However, Open Hemorrhoidectomy demonstrated advantages in direct tissue visualization and precise surgical technique. Conclusion: Minimally Invasive Procedure for Hemorrhoids (MIPH) offers several benefits, including shorter operative duration, reduced postoperative pain, and faster recovery, making it a viable option for patients with hemorrhoids. However, Open Hemorrhoidectomy remains a suitable alternative, particularly in cases where MIPH may not be feasible or contraindicated. Individualized decision-making, considering patient preferences and surgeon expertise, is essential in selecting the optimal surgical approach for hemorrhoidal disease.